Preparation of Amorphous Coatings of AlFeCoNiCuZrV Alloy by Direct Current Magnetron Sputtering Method - Zhang, J.; Zhu, J.B.; Sun, Z.Y.; Li, J.C. (Asian Journal of Chemistry, 2014)
The amorphous coatings of AlFeCoNiCuZrV high entropy alloy were deposited by direct current magnetron sputtering (DCMS) in the mixed atmosphere of Ar and O2. A smooth amorphous coating was obtained. The microstructure and properties of the coatings were investigated. The results showed that the chemical composition, microstructure and mechanical properties of the amorphous coatings intimately relied on the concentration of O2 in the mixture atmosphere. When O2 flow ratio increased, the thickness and roughness of the coatings decreased. The maximum values of the hardness and the elastic modulus of the coating are 12 and 168 Gpa, respectively.